2g+12=22-10g

Simple and best practice solution for 2g+12=22-10g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2g+12=22-10g equation:


Simplifying
2g + 12 = 22 + -10g

Reorder the terms:
12 + 2g = 22 + -10g

Solving
12 + 2g = 22 + -10g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '10g' to each side of the equation.
12 + 2g + 10g = 22 + -10g + 10g

Combine like terms: 2g + 10g = 12g
12 + 12g = 22 + -10g + 10g

Combine like terms: -10g + 10g = 0
12 + 12g = 22 + 0
12 + 12g = 22

Add '-12' to each side of the equation.
12 + -12 + 12g = 22 + -12

Combine like terms: 12 + -12 = 0
0 + 12g = 22 + -12
12g = 22 + -12

Combine like terms: 22 + -12 = 10
12g = 10

Divide each side by '12'.
g = 0.8333333333

Simplifying
g = 0.8333333333

See similar equations:

| 6-tanx=2sec^2x | | x+34=2x+12 | | 3m+13=42-9m | | 3m+13=42-9 | | z^2-26z+169=0 | | 7-3x+6x=40 | | 4+m=-1 | | 2x^3+5x^2-98x+245=0 | | x^2+9x-2=5 | | 4t-3/5-4-2t/3=1 | | -9n+(-2)+3x-n+4= | | 5+4=n | | S^2-145+45=0 | | 5+9s-3=6s+23-4s | | 2x(x-3)+5(x-3)=0 | | 19-n=n-5 | | x=2+3+20-30+60-190+25-30+21 | | 25(e+6.25)=443.75 | | 1x=3x+70 | | X-7-3x=-21 | | 10(e+5)=280 | | Y/-3=1/6 | | x(x-10)=-34 | | -2(x-3)=2-(x+3) | | 3d^2+5d-6=0 | | -16=x+23 | | 5x=9-3 | | -5-2x=3-6 | | 21x+30=20-3 | | x-6=.66666666666666y | | -5x+6=-9x+22 | | 19+x=-16 |

Equations solver categories